Public pension funds and socially responsible investment in South Africa: a case study of the Public Investment Corporation - Luvhengo, victor (Research of GSB, 2018)
Socially responsible investment (SRI) and now commonly known as sustainable responsible investment is starting to gain a momentum in South Africa among asset owners and managers. Of a particular interest is that the leading public pension fund manager, the Public Investment Corporation (PIC) which invests on behalf of the Government Employee Pension Fund (GEPF) has a significant interest in driving this phenomenon in South Africa. In actual fact, GEPF was the first public asset owner in South Africa to subscribe to the United Nations Principles of Responsible Investment in 2006. This is not surprising because a pension fund such as the Government Employees Pension Fund (GEPF) is one of the largest investors through the PIC in the South African economy and the fund is equivalent to 1/3 of the country's GDP with almost R1 trillion assets and has investments in all sectors of the economy. Given the significant power that this fund has in the South African economy, it was of particular interest for this research to link whether SRI agenda in the PIC is also embedded in a broader strategy/policy around South Africa economic development and by whom is this agenda is being driven in the PIC? Furthermore, this research helps to understand the key drivers, challenges, enablers for the PIC to advance SRI agenda in South Africa. The research adopts a case study approach to understand how entrenched is the SRI agenda in big public pension asset managers in South Africa. The research found that over the past few years, the PIC SRI strategy focused on equity and developmental investing with low focus towards fixed income and property asset classes. In general, the research has found that the PIC SRI Strategy responds to issues that that meet government objectives of ensuring growth and economic development of South Africa. In all four asset classes, the PIC SRI Strategy broadly addresses issues such as black economic empowerment, skills development, economic growth, economic and social infrastructure (roads, energy, housing, and education), enterprise development and job creation. However, the government has not taken any concrete steps for greater collaboration with the PIC on ESG issues in South Africa. PIC is advancing its SRI strategy mainly through active share ownership and developmental impact investing.